Larval development in Guancha arnesenae (Porifera, Calcispongiae, Calcinea) - Ereskovsky, A.V.; Willenz, P. (Zoomorphology, 2008)
Larval development and follicle structure of a representative of the Calcinea (Calcispongiae) Guancha arnesenae from the White Sea have been studied for the first time at the ultrastructural level. The follicle in G. arnesenae has an unusual structure: it consists of trapezoid cells rich in phagosomes and a surrounding dense collagen layer. Follicular cells differentiate from choanocytes. Cleavage results in formation of a hollow, equal, non-polarized coeloblastula. Larval morphogenesis occurs by means of direct hollow blastula formation without any individual cell or cell layer movements. The coeloblastula (calciblastula) larva of G. arnesenae is completely ciliated. The larva also contains rare non-ciliated cells: vacuolar cells, bottle-shaped cells and free cells in a central cavity. The basal ciliary apparatus of larval cells includes the basal body, an accessory centriole oriented perpendicularly to it, the basal foot, and two cross-striated rootlets. A bundle of microtubules emerges from the side of the basal body, opposite to the basal foot, running parallel to the outer surface. All bundles of cells are parallel to each other and oriented towards the posterior larval pole, forming a transverse cytoskeletal system. Specialized intercellular junctions in the apical regions of all ciliated cells are revealed for the first time in a Calcispongiae larva. The central larval cavity contains symbiotic bacteria, which are included inside the embryo at the blastula stage.